Combined effects of surface sharpness and transverse curvature on thermal transport in separating flow region. (14th February 2023) - Mehmood, Ahmer; Shah, Babar Hussain; Raza, Iqrar
Abstract: Heat transfer analysis in a retarded laminar boundary layer over bodies of revolution with a variable radius subject to retarded surface temperature is presented. This study focuses to develop numerical data for local Nusselt number N ux under the influence of retarded free stream velocity and decreasing surface temperature along with body contour and surface transverse curvature. With the use of such retarded velocities and body contour the similarity of flow phenomenon does not sustain, and the problem becomes non-similar in nature which has been solved using an efficient numerical scheme, commonly known as Keller-Box. The effects of pertinent parameters such as exponent of free stream velocity m, exponent of surface temperature q, body contour n, and surface transverse curvature k on temperature profile, rate of heat transfer at the surface, and energy thickness of thermal boundary layer are presented through various graphs and tables. The rate of heat transfer and the energy thickness of the thermal boundary layer are observed to decrease with increasing levels of retardation. Furthermore, the rate of heat transfer decreases as the body contour parameter increases, whereas the surface transverse curvature parameter exhibits the opposite trend.